2019
DOI: 10.1038/s41598-019-53671-8
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin impacts Tumor Angiogenesis and Outcome in Thymic Epithelial Tumors

Abstract: Tumor angiogenesis is a key factor in the progression of thymic epithelial tumors (TETs). Activin A, a member of the TGFβ family, and its antagonist Follistatin are involved in several human malignancies and angiogenesis. We investigated Activin A and Follistatin in serum and tumor tissue of patients with TETs in relation to microvessel density (MVD), WHO histology classification, tumor stage and outcome. Membranous Activin A expression was detected in all tumor tissues of TETs, while Follistatin staining was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…TET, a rare malignant tumor of the chest, is the most common anterior mediastinal neoplasm in adults, with an incidence rate of 1.5-3.2 cases per million people per year (36). Among TETs, thymomas are often uniquely associated with autoimmune diseases, whereas thymic carcinomas exhibit more invasive characteristics in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…TET, a rare malignant tumor of the chest, is the most common anterior mediastinal neoplasm in adults, with an incidence rate of 1.5-3.2 cases per million people per year (36). Among TETs, thymomas are often uniquely associated with autoimmune diseases, whereas thymic carcinomas exhibit more invasive characteristics in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…TET, a malignant tumor in the chest, is most common, albeit rare, in adult anterior mediastinal neoplasms, with an incidence rate of only 1.5-3.2 cases per 1000,000 people per year . [37] Among TETs, thymomas are often uniquely associated with autoimmune diseases, whereas thymic carcinoma exhibits more invasive characteristics in the clinic. A study by Radovich et al reported a strong association of broad histological subtypes (A, AB, B, and thymic carcinoma) with multiple classes of aberrations that occur at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…In physiological conditions, FST is involved in regulating reproduction, pregnancy, inflammation, metabolism and stress response [30][31][32]44]. Additionally, FST also has a well-known antitumorigenic role [45][46][47]. Chen et al described FST as a novel biomarker for LADC and their findings suggested that circulating FST might be directly secreted by LADC cells in order to neutralize ActA [48].…”
Section: Discussionmentioning
confidence: 99%